Analysis of Factors Influencing The Acceptance and Adoption of Starlink Internet Services in Indonesia - Via Amalia Lesmana; Nabilah Ananda Razani (Dinasti Publisher, 2025)
This study aims to examine the extent of Indonesian society's acceptance of Starlink amidst the convenience of existing internet services and identify the factors influencing its adoption. A quantitative approach was employed using SPSS data processing, with online questionnaires and interviews as the primary data collection methods. Data analysis was conducted by surveying respondents who use Starlink to assess their level of acceptance. The findings indicate that overall acceptance of Starlink remains relatively low, with statistical influences from factors such as age, gender, cost, and the type of internet service currently in use. As internet service demand continues to rise, Starlink offers a high-quality, low-latency satellite-based internet solution capable of reaching remote areas. However, its acceptance and adoption are not entirely positive and are influenced by various factors. This study concludes that only certain factors significantly impact Starlink’s acceptance, although the overall perception remains relatively positive, with users tending to fall into the early majority category. Most Indonesians still rely on cable and mobile internet services. Therefore, this study suggests that Starlink should develop effective strategies to enhance awareness and education on satellite-based internet usage, particularly in regions that prefer cable and mobile internet due to its affordability and accessibility.